USE OF COMMUNICATION STRATEGIES IN PALLIATIVE CARE IN BRAZIL: INTEGRATIVE REVIEW - Kelviani Ludmila dos Santos Almeida; Dayse Maioli Garcia (Universidade Federal do Paraná, 2015)
Palliative care is a comprehensive care field served by a multidisciplinary team. Communication is an essential tool for this approach. Through it an adequate control of symptoms, as well as individualized and quality care can be offered, so that conflicts and anxieties can be solved and autonomy preserved. The proposed objective was to identify communication strategies used in Brazil for patients in palliative care. An integrative review was developed wherein articles were located in four databases and a portal of theses in the period from 2009 to 2014. The articles relevant to the topic totaled 19, from which 16 were used. The results showed that the most frequently cited strategies were active listening, therapeutic silence, and affective touch, hearing, and empathy. However, even though recognized by the literature, the use of this method is still rare, and professionals need emerging training in the palliative approach.